Field evaluation of subgrade soils under dynamic loads using orthogonal earth pressure transducers - Lin, Peiyuan (2021)
Subgrade soils experience repeated traffic loads, such that dynamic stress and displacement are accumulated to jeopardize the stability of pavement foundations. Laboratory element testing is often conducted to apply cyclic loads to the soil. In fact, the stress state of subgrade soil is complex due to the constant rotation of principal stress induced by moving vehicles. It is hard to select constitutive relations for unsaturated subgrade soils in numerical or analytical calculation, since most models are developed without proper consideration of principal stress rotation. Furthermore, most available earth pressure sensors cannot provide stress measurements in three orthogonal directions for a soil element at the same time. A novel orthogonal earth pressure transducer is developed to measure dynamic stresses of subgrade soils in three directions under a roadway at Chencun, China. The cumulative effect of dynamic stress with load cycles is observed explicitly. Results indicate that the dynamic stress becomes negligible at 2 m from the roadway, and stabilization is suggested to be limited within this width. A series of constitutive relations is proposed to correlate the dynamic stress with the resulted displacement in different directions, which can be used to guide the design of unsaturated subgrade soils in South China.